Factors affecting the periapical healing process of endodontically treated teeth (Journal of Applied Oral Science, 2017)
Tissue repair is an essential process that reestablishes tissue integrity and regular function. Nevertheless, different therapeutic factors and clinical conditions may interfere in this process of periapical healing. This review aims to discuss the important therapeutic factors associated with the clinical protocol used during root canal treatment and to highlight the systemic conditions associated with the periapical healing process of endodontically treated teeth. The antibacterial strategies indicated in the conventional treatment of an inflamed and infected pulp and the modulation of the host's immune response may assist in tissue repair, if wound healing has been hindered by infection. Systemic conditions, such as diabetes mellitus and hypertension, can also inhibit wound healing. The success of root canal treatment is affected by the correct choice of clinical protocol. These factors are dependent on the sanitization process (instrumentation, irrigant solution, irrigating strategies, and intracanal dressing), the apical limit of the root canal preparation and obturation, and the quality of the sealer. The challenges affecting the healing process of endodontically treated teeth include control of the inflammation of pulp or infectious processes and simultaneous neutralization of unpredictable provocations to the periapical tissue. Along with these factors, one must understand the local and general clinical conditions (systemic health of the patient) that affect the outcome of root canal treatment prediction.